2020
DOI: 10.3389/fmed.2020.584250
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intra-Tumoral Vascularization in Hepatocellular Carcinomas

Abstract: Intratumoral neovascularization has intricate effects on tumor growth, metastasis, and treatment. Over the last 30 years, Microvessel density (MVD) has been the standard method for laboratory and clinical evaluation of angiogenesis. Hepatocellular carcinoma (HCC) is a typical hypervascularized tumor, and the predictive value of MVD for prognosis is still controversial. According to previous viewpoints, this has been attributed to the determination of hotspot, counting methods, vascular endothelial markers, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 89 publications
0
19
0
1
Order By: Relevance
“…Third, this study did not evaluate the plasma levels of these three angiogenesis factors in normal control subjects or cirrhotic patients because we focused on the role of Ang-1, Ang-2, and VEGF as prognostic rather than diagnostic markers. Fourth, this study did not evaluate other valuable angiogenesis markers, such as microvessel density, PDGF/PDGFR, FGF/FGFR, and endoglin (CD105)[ 9 , 31 ]. Further comprehensive studies including these angiogenesis markers are hence needed.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this study did not evaluate the plasma levels of these three angiogenesis factors in normal control subjects or cirrhotic patients because we focused on the role of Ang-1, Ang-2, and VEGF as prognostic rather than diagnostic markers. Fourth, this study did not evaluate other valuable angiogenesis markers, such as microvessel density, PDGF/PDGFR, FGF/FGFR, and endoglin (CD105)[ 9 , 31 ]. Further comprehensive studies including these angiogenesis markers are hence needed.…”
Section: Discussionmentioning
confidence: 99%
“…The better understanding of the molecular basis of this pathology is crucial for the recognition of new molecular targets, treatment decisions and biomarkers [193,194]. HCC is a typical hyper-vascular tumor which uses exosomes enriched in angiogenic factors including miRNAs for cancer progression and metastasis [195]. Recently, it was found that miR-1290 delivered through exosomes from HCC cells to recipient endothelial cells downregulates the suppressor of MEK null (SMEK1) expression and promotes tumor angiogenesis [196].…”
Section: Liver Cancermentioning
confidence: 99%
“…HCC is a highly vascularized malignancy [ 46 ], but there are conflicting data with regard to microvessel density (MVD) and microvascular invasion (MVI) as predictive indicators for patient prognosis [ 46 , 47 ]. One possible explanation for these discrepant results is that the amount of vascular ITH may influence tumor behavior independent from the degree of MVD or MVI.…”
Section: Tumor Microenvironment Ithmentioning
confidence: 99%